Kajian Pembuatan Film Plastik Biodegradable Dari Ekstrak Bonggol Jagung - Mukhlisien Mukhlisien; Suhendrayatna Suhendrayatna; Mohd Montazeri; Hasnil Amar (Jurnal Inovasi Ramah Lingkungan, 2021)
Indonesia as the second largest contributor for plastic waste, this is because most plastics are made from petroleum that it takes hundred years to unravel them. Bioplastic is one of the solution for the problem that caused environmental pollution by plastic waste. Bioplastics are plastics that are made from raw materials of starch derived from tubers and vegetables that naturally decomposed. The used of corncob starch because it has potential starch content and utilized waste food. The problem was the tensile testing of bioplastic did not match the convensional plastic standard. Therefore research varies corncob starch extract 3,5,7gr and varies gliserol plasticizer concentration 2, 3 and 4ml. Bioplastic then analyzed with tensile test, , water resistance test and biodegradable test. Optimum results was obtained with tensile strength 79.5 MPa. Optimum elongation 86 %. Water resistance optimum value 30,76%,  and biodegradable test  will degraded in 28 days. The overall value is included in the range of SNI values.